Controllable preparation and catalytic performance of Pt/metal oxide nanocomposites for glycerol hydrogenation. (2nd January 2017) - Wang, Hongmei; Lu, Zhufeng; Li, Chunhe; Lu, Dingze; Wang, Xiao
Abstract: A surfactant-free and facile one-pot synthetic route in the alkaline glycol system has been developed for the fabrication of Pt/metal oxide nanocomposites. The structure and chemical composition of the as-prepared products were characterised by X-ray diffraction (XRD), transmission electron microscopy (TEM) and inductively coupled plasma-mass spectrometry (ICP-MS). It is found that the corresponding precursors have been completely converted into the Pt/metal oxide nanocomposites. As for Pt/ZnO nanocomposites, the Pt loading amount can be controlled by the different molar ratios of Pt and Zinc precursor, while Pt nanoparticle sizes can be adjusted through the different mass of NaHCO3 added. In addition, the catalytic activities of Pt/metal oxide nanocomposites for glycerol hydrogenation were also studied. When the amount of platinum metal was kept constant, different metal oxide supporters demonstrated different levels of catalytic activation. The diverse reason of the catalytic activation for the different Pt/metal oxide nanocomposites was also speculated.